Physical and psychological changes of the COVID-19 infodemic by the older adult population - Raísa Gonçalves Aquino; Eliane da Silva Pereira; Priscilla Alfradique de Souza; Graziele Ribeiro Bitencourt; Rosimere Ferreira Santana; Elaine Cristina Rodrigues da Costa; Ricardo Bezerra Cavalcante (Revista Brasileira de Enfermagem, 2024)
ABSTRACT Objective: to analyze the physical and psychological changes of the COVID-19 infodemic for the older adult population of Rio de Janeiro. Method: a cross-sectional, web-based survey to find out about access to news and information about COVID-19 among older adult in Rio de Janeiro, between July and December 2020. Univariate analysis and bivariate analysis were carried out using non-parametric statistical methods. Results: 390 older adults took part, predominantly female (75.1%), aged between 66 and 75 (35.4%), married (51.0%), white (60.3%), owning their own home (81.8%), located in urban areas (91%), with complete or incomplete primary education (31.8%) and retired or pensioners (79.2%). Younger people were significantly affected both physically and psychologically by social networks when compared to television (<0.001). Conclusion: Physical and psychological changes from exposure to information about COVID-19 have affected the lives of the older adult, having an impact on this population.